2019
DOI: 10.1002/jemt.23211
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements bioaccumulation inPorcellionides pruinosus(Brandt, 1833) and related biomarkers of exposure

Abstract: In the last years, the increase of anthropogenic activities has led to a progressive pollution of ecosystems. Oniscidean isopods are a group of terrestrial animals known as excellent bio‐indicators and bio‐accumulators, because of their capacity to accumulate contaminants and to implement appropriate strategies of detoxification. For this study, we collected Porcellionides pruinosus from two different sites in the Corinth region (Greece), a polluted site and a control site, to assess the heavy metal pollution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Terrestrial isopods are now accepted as excellent bioindicators for the study of soil contamination levels from heavy metals (Droutsa et al, ; García‐Hernández et al, ; Longo et al, ) or organic compounds (Agodi et al, ). Additionally, they can be collected without difficulty, as they are widely distributed all over the world, have a relatively short life span, reproduce rapidly at high rates and are sensitive to pollutants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terrestrial isopods are now accepted as excellent bioindicators for the study of soil contamination levels from heavy metals (Droutsa et al, ; García‐Hernández et al, ; Longo et al, ) or organic compounds (Agodi et al, ). Additionally, they can be collected without difficulty, as they are widely distributed all over the world, have a relatively short life span, reproduce rapidly at high rates and are sensitive to pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Terrestrial isopods represent an abundant and widespread component of the fauna of the soil (Caruso, Baglieri, Di Maio, & Lombardo, ; Messina, Montesanto, Pezzino, Caruso, & Lombardo, ; Messina, Pezzino, Montesanto, Caruso, & Lombardo, ), being very sensitive to the effects of anthropogenic activities, and they are widely used as models for studies of this type, as bioindicators of environmental pollution (Agodi et al, ; Longo, Trovato, Mazzei, Ferrante, & Oliveri Conti, ; Mazzei et al, ). Furthermore they present an organ primarily involved in the accumulation of xenobiotics (Costa, Bouchon, Van Straalen, Sousa, & Ribeiro, ; Hussein, Obuid‐Allah, Mohammad, Scott‐Fordsmand, & Abd El‐Wakeil, ; Longo et al, ; Mazzei et al, ), the hepatopancreas and a detoxification system of heavy metals which involves the induction of the expression of the metallothioneins (Droutsa et al, ; Mazzei et al, ). Metallothioneins 1 (MT1) are called exposure biomarkers and are part of a superfamily of low molecular mass cytoplasmic proteins, characterized by a high cysteine content and the absence of aromatic aminoacids and histidine, that are involved in the regulation of essential metals metabolism, in heavy metal detoxification and in protection against oxidative stress (Ferrante et al, ; Salvaggio et al, ; Viarengo, Burlando, Ceratto, & Panfoli, ) and also in metallic nanoparticles detoxification (Brundo et al, ; Pecoraro, Marino, et al, ; Pecoraro, Salvaggio, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…After euthanized with MS‐222 (0.7 g/L), zebrafish eyes were taken and samples were prepared from paraffin‐embedded tissue for histologically stained sections (Brundo et al, ; Droutsa et al, ; Salvaggio et al, ). Samples were fixed in 4% paraformaldehyde in 0.1 M phosphate buffer, pH 7.4 for 24 hr at room temperature (RT), dehydrated in ethanol followed by xylene, and embedded in paraffin 4–5 μm.…”
Section: Methodsmentioning
confidence: 99%
“…After euthanized with MS-222 (0.7 g/L), zebrafish eyes were taken and samples were prepared from paraffin-embedded tissue for histologically stained sections (Brundo et al, 2011;Droutsa et al, 2019;Salvaggio et al, 2017…”
Section: Histologymentioning
confidence: 99%
“…These biomarkers, used in previous studies, have proved excellent biomarkers of exposure to metallic xenobiotic in different animals (Droutsa et al, ; Ferrante et al, ; Mazzei et al, ; Piscopo et al, ; Salvaggio et al, ); they have been chosen because it has been shown that they intervene in the detoxification processes of metallic nanoparticles (Brundo et al, ; Pecoraro, Marino, et al, ; Pecoraro, Salvaggio, et al, ).…”
Section: Introductionmentioning
confidence: 99%